Pengaruh Auditor Switching, Komite Audit, dan Audit Capacity Stress terhadap Kualitas Audit - Putri Handayani; Mia Angelina Setiawan (Jurnal Eksplorasi Akuntansi, 2024)
This research aimed to examine the effect of auditor switching, audit committee and audit capacity stress on audit quality. The population in this research are all financial sector companies listed on the Indonesia Stock Exchange in 2018-2020. The sampling technique used was purposive sampling. Total samples is 255 companies. The statistical method used logistic regression analysis. The results show that auditor switching, audit committee and audit capacity stress have no effect on audit quality in financial sector companies listed on the Indonesia Stock Exchange in 2018-2020.